2017
DOI: 10.18290/rpsych.2017.20.1-4pl
|View full text |Cite
|
Sign up to set email alerts
|

Wsparcie i zmagania religijne jako predyktory jakości życia Anonimowych Alkoholików – moderacja przez czas abstynencji

Abstract: The aim of the study was to analyze the connection between religious comfort and struggle and quality of life in Alcoholics Anonymous. The interaction effect of the length of abstinence and religious variables on the quality of life was tested as well. The participants were 100 members of an Alcoholics Anonymous group. We used the Religious Comfort and Strain Scale by Yali, Exline, Wood, and Worthington and the Quality of Life Questionnaire for Adults by Schalock and Keith. The correlation analysis showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…This is in line with the view of “the cumulative stress effect.” If religion stops working as a personal resource—if, on the contrary, it generates stress—then stress accumulates (cf. Hobfoll 2001 ) and impairs mental health (Zarzycka 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the view of “the cumulative stress effect.” If religion stops working as a personal resource—if, on the contrary, it generates stress—then stress accumulates (cf. Hobfoll 2001 ) and impairs mental health (Zarzycka 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relationship between struggle and psychological distress is stronger in people living alone than in those in marriages (Ellison and Lee 2010), in younger people than in older people (Ellison and Lee 2010; Krause et al 1999), and in the sick and abused than in healthy controls (Pargament et al 2006). Moreover, studies confirmed that religious struggle mediates the relationship between stress and health: in people with few problems, religious guilt and a negative opinion about God mitigate negative mental health symptoms but are escalated when the stress perceived is high (Zarzycka 2017). Identification with a specific church or tradition also moderates dependencies between religious struggle and health symptoms (Ellison et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…The first is the concept of religious coping, which defines struggle as a specific, negative form of religious coping elicited by various life stressors (Pargament et al 2000). The second perspective defines struggle as a dispositional category; that is, a generalized tendency to experience strains related to religious beliefs and experience and not as a reaction related to religious coping (Exline 2013; Zarzycka 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations